Implementasi Manajemen Sumber Daya Manusia Di Fasilitas Kesehatan: Kajian Studi Literatur - Jacqueline Makanoneng; Sri Sundari; Marisi Pakpahan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Health human resource management is a crucial aspect in efforts to improve the level of public health and improve the quality of services in health facilities. Health resources play a key role in the transformation of health development in Indonesia. Good implementation of health service management in health facilities is needed so that health development in Indonesia can run optimally. This research uses a literature review method with an article search strategy via Google Scholar. Articles were selected based on the inclusion criteria in this study. The research results show that the implementation of health human resource management in health facilities is still not optimal, which causes a shortage and inequality of health human resources in these facilities. The government and related agencies are expected to be able to improve the health resource management system by analyzing health human resource needs. In addition, efforts need to be made to educate and distribute health human resources in health facilities to ensure more equitable and quality health services.